2005
DOI: 10.1016/j.febslet.2005.02.061
|View full text |Cite
|
Sign up to set email alerts
|

BLG‐e1 – A novel regulatory element in the distal region of the β‐lactoglobulin gene promoter

Abstract: b-Lactoglobulin (BLG) is a major ruminant milk protein. A regulatory element, termed BLG-e1, was defined in the distal region of the ovine BLG gene promoter. This 299-bp element lacks the established cis-regulatory sequences that affect milk-protein gene expression. Nevertheless, it alters the binding of downstream BLG sequences to histone H4 and the sensitivity of the histone-DNA complexes to trichostatin A treatment. In mammary cells cultured under favorable lactogenic conditions, BLG-e1 acts as a potent, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The promoter of the milk protein gene (ovine or caprine beta-lactoglobulin) has been used to target high level expression of foreign protein in the milk of transgenic mice [2023]. In our previous study, the strategy of a BLG/CMV based vector efficiently drove the human lactoferrin cDNA gene to express in the milk of transgenic mice [7].…”
Section: Discussionmentioning
confidence: 99%
“…The promoter of the milk protein gene (ovine or caprine beta-lactoglobulin) has been used to target high level expression of foreign protein in the milk of transgenic mice [2023]. In our previous study, the strategy of a BLG/CMV based vector efficiently drove the human lactoferrin cDNA gene to express in the milk of transgenic mice [7].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, tissue pieces were washed, collected and sonicated on ice (SONICS Vibra cell, Newtown, CT) in 500 μl SDS lysis buffer. DNA was sheared to lengths of between 200 and 1,000 bp and ChIP was performed with anti‐acetyl histone H4 polyclonal antibodies (Upstate) diluted 1:200 as previously described 40. DNA‐protein crosslinking was reversed at 65°C for 4 hr in the presence of 5 M NaCl and DNA was recovered by phenol/chloroform extraction and ethanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from the inguinal and thoracic mammary glands with TRIZOL (Gibco/BRL, Gaithersburg, MD) as previously described. 40 DNase-I-treated aliquots (0.2 lg) were reverse-transcribed using a superscript II reverse transcriptase (RT) kit and oligo(dT) primers (Invitrogen, Carlsbad, CA) according to the manufacturer's protocol.…”
Section: Rna Extraction and Reverse Transcriptionmentioning
confidence: 99%
“…Bioactive foreign proteins have been expressed specifically in the mammary gland under the direction of specific milk regulatory sequences (Liu et al, 2012). These include sequences obtained from goat β‐casein (Pohlmeier et al, 2011), bovine αs1‐casein (Ebert et al, 1994; Serova et al, 2012), and ovine β‐lactoglobulin (BLG; Barash et al, 1999; Reichenstein et al, 2005; Khodarovich et al, 2008), which contain binding sites for transcription factors such as the signal transducer and activator of transcription 5 (STAT5), CCAAT enhancer‐binding protein (C/EBP), nuclear factor I (NF‐I), glucocorticoid receptor (GR), E26‐specific sequence factor (Ets), and octamer‐binding transcription factor‐1 (Oct‐1; Reichenstein et al, 2005; Benlhabib and Herrera, 2006). Previous studies have shown that only a small percentage of cells in the mammary glands from a transgenic animal express recombinant protein, thus a more efficient mammary gland‐specific vector remains to be devised (Pantano et al, 2003; Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%